UPAYA DINAS SOSIAL MENGATASI KENAKALAN REMAJA MENGKONSUMSI MINUMAN KERAS DI KOTA SUNGAI PENUH. (STUDI KASUS: REMAJA YANG MENGKONSUMSI MINUMAN KERAS DI PASAR SUNGAI PENUH) - Monita, Selyfia; Yuhelna, Yuhelna; Yatim, Yenita (Universitas Tanjungpura, 2022)
Consuming liquor has a very bad impact on the lives of teenagers, both physically, psychologically, and socially, efforts need to be made to overcome this, not only the role of parents, but the government of course also participates in overcoming this problem, one of the government agencies which plays a role in overcoming juvenile delinquency, namely the social service. The purpose of the study was to describe the efforts of social services to overcome juvenile delinquency consuming liquor in the city of Sungai Penuh. The theory used in this study is the structural functional theory proposed by Talcot Parson. The research was conducted at the social office of Sungai Penuh City. This study used a qualitative research method with a descriptive type of research. The withdrawal of informants was carried out by purposive sampling technique. The data collection method in this study began with observation, interviews, and document studies. Data analysis techniques in research can be carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that there were several efforts made by the Sungai Penuh City Social Service in Overcoming Adolescents who consume liquor. including: 1) Providing socialization to adolescents regarding the dangers of consuming liquor. 2) Give sanctions/punishments. and 3) Conducting Rehabilitation.